Metal‐Catalyzed Abiotic Cleavage of C═C Bonds for Effective Fluorescence Imaging of Cu(II) and Fe(III) in Living Systems - Chunfei Wang; Dandan Chen; Zixiang Wei; Jingyun Tan; Changfeng Wu; Xuanjun Zhang (Advanced Science)
Abstract Imaging abnormal copper/iron with effective fluorescent tools is essential to comprehensively put insight into many pathological events. However, conventional coordination‐based detection is mired in the fluorescence quenching induced by paramagnetic Cu(II)/Fe(III). Moreover, the strong chelating property of the probe will consume dissociative metal ions and inevitably interfere with the physiological microenvironment. Here, a new strategy is developed by employing this aberrant Cu(II)/Fe(III) to catalyze bond cleavage for fluorescent imaging of them. A short series of near‐infrared fluorescent molecules (NIRB1−NIRB6) is devised as substrates, wherein the specific C═C bonds can be effectively cleaved to activate red fluorophore by Cu(II)/Fe(III) catalyzing. Representatively, NIRB1 is applied for fluorescent imaging of Cu(II)/Fe(III) in living cells, zebrafish, and Alzheimer's disease (AD)‐afflicted mouse brains which is of significance to monitor metal safety. The successful cleavage of C═C bonds catalyzed by Cu(II)/Fe(III) enriches the application of abiotic bond cleavage reactions in metal detection, and may also inspire the development of fluorescent tools for the future diagnosis and therapy of diseases.